Α-Ketoglutarate Accumulation Is Not Dependent on Isocitrate Dehydrogenase Activity during Tellurite Detoxification in Escherichia coli. (25th November 2013) - Reinoso, Claudia A.; Appanna, Vasu D.; Vásquez, Claudio C.
Abstract : Tellurite is toxic to most microorganisms because of its ability to generate oxidative stress. However, the way in which tellurite interferes with cellular processes is not fully understood to date. In this line, it was previously shown that tellurite-exposed cells displayed reduced activity of the α -ketoglutarate dehydrogenase complex ( α -KGDH), which resulted in α -ketoglutarate ( α -KG) accumulation. In this work, we assessed if α -KG accumulation in tellurite-exposed E. coli could also result from increased isocitrate dehydrogenase (ICDH) and glutamate dehydrogenase (GDH) activities, both enzymes involved in α -KG synthesis. Unexpectedly both activities were found to decrease in the presence of the toxicant, an observation that seems to result from the decreased transcription of icdA and gdhA genes (encoding ICDH and GDH, resp.). Accordingly, isocitrate levels were found to increase in tellurite-exposed E. coli . In the presence of the toxicant, cells lacking icdA or gdhA exhibited decreased reactive oxygen species (ROS) levels and higher tellurite sensitivity as compared to the wild type strain. Finally, a novel branch activity of ICDH as tellurite reductase is presented.